2011
DOI: 10.1097/fjc.0b013e3182244a51
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Disorders and Oxidative Stress Programming in Offspring of Rats Fed a High-fat Diet During Lactation: Effects of a Vinifera Grape Skin (ACH09) Extract

Abstract: This study examined the effect of Vitis vinifera grape skin ACH09 extract (ACH09) on metabolic disorders and oxidative stress in adult offspring of rats fed a high-fat diet (HF) during lactation. Four groups of female rats were fed: control diet (7% fat); ACH09 (7% fat + 200 mg·kg·d ACH09 orally); HF (24% fat); HF+ ACH09 (24% fat + 200 mg·kg·d ACH09 orally) during lactation. From weaning onward, all female offspring were fed a control diet and killed when they were 90 or 180 days old. Systolic blood pressure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 47 publications
4
37
0
Order By: Relevance
“…Different studies have shown that the administration of polyphenols to dams during prenatal and early postnatal periods can exert beneficial effects on body fat gain and different metabolic disorders, such us dyslipidaemia, insulin resistance and inflammation, on their offspring in later life [15][16][17]19]. However, in most of these studies, the metabolic programming effects of polyphenols have been observed after the administration of these compounds at high doses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies have shown that the administration of polyphenols to dams during prenatal and early postnatal periods can exert beneficial effects on body fat gain and different metabolic disorders, such us dyslipidaemia, insulin resistance and inflammation, on their offspring in later life [15][16][17]19]. However, in most of these studies, the metabolic programming effects of polyphenols have been observed after the administration of these compounds at high doses.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that these bioactive food compounds can reach the foetuses and placentas of pregnant rats [11]. Furthermore, recent studies have shown that polyphenols can exert metabolic programming effects on the offspring through maternal intake [12][13][14][15][16][17][18][19][20]. For example, genistein was effective in preventing body weight gain of the offspring when administered during pregnancy and lactation [12,14] but also exerted harmful effects related to anxiety, aggressive behaviours, spatial learning and reproductive development [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also evidence that grape skin extracts could decrease glucose levels and insulin resistance in high fat‐fed rats (Emiliano et al, ). This extract (200 mg/kg/day orally) decreased the insulin resistance in diabetic mice independent of an increase in insulin release but dependent on an increase in insulin sensitivity, and it did not change glucose‐induced insulin secretion in isolated pancreatic islets (Soares de Moura et al, ).…”
Section: The Effects Of Grapes On Metabolic Syndromementioning
confidence: 99%
“…Not only clinical trials but also animal studies confirm the beneficial effects of grape polyphenols for lowering blood pressure. Grape skin extract decreased high systolic blood pressure in offspring of rats fed a high‐fat diet during lactation (Emiliano et al, ).…”
Section: The Effects Of Grapes On Metabolic Syndromementioning
confidence: 99%